2003
DOI: 10.1007/s10582-003-0013-z
|View full text |Cite
|
Sign up to set email alerts
|

Variations of iodine-129 activities in various seaweed collected on the French channel coast

Abstract: 1291, the only natural radioactive isotope of iodine (Tu2 = 15.Tx106a), has been artificially produced since the end of the forties by the different nuclear, civil as well as military, activities leading to an increase of the background levels especially in the Northern hemisphere. In the marine environment, seaweed is known to accumulate iodine isotopes at high concentration levels. 16 seaweed species were collected at Goury (France), under the direct influence of discharges of authorised low-level radioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Gamma and X-ray spectrometry have been used to measure 129 I in thyroid, urine, seaweed, and nuclear waste by using HpGe or plenary Si detector [104][105][106][117][118]. This is based on the counting the 39.6 keV γ-ray or 29.46+29.48 keV (58.1%) X-rays.…”
Section: Gamma and X-ray Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Gamma and X-ray spectrometry have been used to measure 129 I in thyroid, urine, seaweed, and nuclear waste by using HpGe or plenary Si detector [104][105][106][117][118]. This is based on the counting the 39.6 keV γ-ray or 29.46+29.48 keV (58.1%) X-rays.…”
Section: Gamma and X-ray Spectrometrymentioning
confidence: 99%
“…This is based on the counting the 39.6 keV γ-ray or 29.46+29.48 keV (58.1%) X-rays. Due to the low counting efficiency of gamma detector (< 2%), low γ-ray abundance (7.5%), and high background, a detection limit of 20-200 mBq was obtained [104,[117][118] depending on the level of interfering radionuclide. In addition, due to the low energy of X-γ rays (29-40 keV) and normally big sample used (50 -500 g), elaborative self-absorption correction has to be carried out in order to obtain accurate results.…”
Section: Gamma and X-ray Spectrometrymentioning
confidence: 99%
“…However, the detection limit of this method is still higher than 20 mBq (or 3 ng), even for the separated iodine samples. Therefore this technique is normally used for the measurement of 129 I of high concentration, such as that in thyroid and seaweed collected in the high contaminated area, and in nuclear waste [16,31].…”
Section: γ-And X-ray Spectrometrymentioning
confidence: 99%
“…The concentration factors for other seaweed species (green and red algae species) were lower; the authors linked this interspecies difference to different growth levels of each species (the brown alga L. digitata grows at the lowest levels of the shore and therefore represents the highest concentration factors), but 129 I activities and 129 I/ 127 I ratios of different seaweed species did not show any gradient following their vertical distribution. They concluded that the contact time of the seaweed with contaminated water had less impact on their 129 I level than their physiological ability to incorporate iodine (Fréchou and Calmet, 2003a).…”
Section: Levels Of 127 I and 129 I Determinedmentioning
confidence: 99%
“…Therefore brown algae can be used to monitor the activity level of 129 I in the marine environment (Fréchou and Calmet, 2003a).…”
Section: Introductionmentioning
confidence: 99%